Higher scanning frequency is correlated with less fear of hypoglycemia in type 1 diabetes patients using isCGM - Jerzy Hohendorff; Jerzy Hohendorff; Przemyslaw Witek; Przemyslaw Witek; Michal Kania; Michal Kania; Maria Sudol; Katarzyna Hajduk; Adam Stepien; Katarzyna Cyganek; Katarzyna Cyganek; Beata Kiec-Wilk; et al. (Frontiers in Endocrinology, 2022)
BackgroundFrequent scanning of intermittently scanned continuous glucose monitoring (isCGM) devices is associated with improvements in glycemic indices. Limited data is available for its correlation with fear of hypoglycemia (FOH), an established factor affecting quality of life and glycemic control in type 1 diabetes (T1DM).AimThe aim of the study was to analyze the association of sensor scanning frequency with FOH and glycemic indices in T1DM patients using isCGM.Subjects and methodsT1DM patients using isCGM were eligible. Clinical data and Ambulatory Glucose Profile (AGP) reports were obtained from medical records. At outpatient visits, AGP of last 14 days prior to visit were analyzed and FOH was assessed using Hypoglycemia Fear Survey II (HFS II).ResultsWe included 77 consecutive T1DM patients (58 females, 19 males). Mean age was 34.1 ± 10.2 years and mean T1DM duration was 14.7 ± 12.0 years. Baseline mean glycemic indices were as follows: mean glucose - 155.8 ± 29.8 mg/dL; GMI - 53.3 ± 7.5 mmol/mol; TIR - 66.4 ± 17.8%; TBR70 - 4.5 ± 4.1%; TBR54 - 0.6 ± 1.2%; TAR180 - 29.2 ± 17.9%; TAR250 - 9.6 ± 10.4%; %CV - 36.7 ± 8.3. Average scanning frequency was 13.8 ± 7.8 scans/day. Mean HFS II scores were 16.1 ± 7.2 and 18.7 ± 12.2 in behavior and worry subscale, respectively. Correlation was confirmed between scanning frequency and mean glucose, GMI, TIR, TBR70, TAR180, TAR250, %CV and HFS II total, and HFS II - B (p<0.05 for all statistics).ConclusionsFor the first time, we report that higher scanning frequency is associated not only with better glycemic indices but also with less FOH in T1DM adult patients using isCGM.